The patient general satisfaction of mandibular single-implant overdentures and conventional complete dentures: Study protocol for a randomized crossover trial - Kanazawa, Manabu (Medicine (Baltimore), 2018)
BACKGROUND: Mandibular overdentures retained by a single implant placed in the midline of edentulous mandible have been reported to be more comfortable and function better than complete dentures. Although single-implant overdentures are still more costly than conventional complete dentures, there are a few studies which investigated whether mandibular single-implant overdentures are superior to complete dentures when patient general satisfaction is compared. The aim of this study is to assess patient general satisfaction with mandibular single-implant overdentures and complete dentures. METHODS: This study is a randomized crossover trial to compare mandibular single-implant overdentures and complete dentures in edentulous individuals. Participant recruitment is ongoing at the time of this submission. Twenty-two participants will be recruited. New mandibular complete dentures will be fabricated. A single implant will be placed in the midline of the edentulous mandible. The mucosal surface of the complete denture around the implant will be relieved for 3 months. The participants will then be randomly allocated into 2 groups according to the order of the interventions; group 1 will receive single-implant overdentures first and will wear them for 2 months, followed by complete dentures for 2 months. Group 2 will receive the same treatments in a reverse order. After experiencing the 2 interventions, the participants will choose one of the mandibular prostheses, and yearly follow-up visits are planned for 5 years. The primary outcome of this trial is patient ratings of general satisfaction on 100 mm visual analog scales. Assessments of the prostheses and oral health-related quality of life will also be recorded as patient-reported outcomes. The secondary outcomes are cost and time for treatment. Masticatory efficiency and cognitive capacity will also be recorded. Furthermore, qualitative research will be performed to investigate the factors associated with success of these mandibular denture types. Clinical outcomes, such as implant survival rate, marginal bone loss, and prosthodontic complications, will also be recorded. DISCUSSION: The results of this randomized crossover trial will clarify whether mandibular single implants and overdentures for edentulous individuals provide better patient general satisfaction when compared to conventional complete dentures. TRIAL REGISTRATION: This clinical trial was registered at the University Hospital Medical Information Network (UMIN) Center (UMIN000017883).